APPROACHES TO INTERCULTURAL EDUCATION AND LEARNING IN GERMANY IN THE CONTEXT OF INTEGRATION (Pedagogy of Higher and Secondary Education, 2011)
The article deals the problem of interciltural teaching in Germany on the conditions of European integration and migration of great groups of people.
Keywords: intercultural education; foreign language education; intercultural aspect of foreign languages teaching